Characterization of prolactin-releasing peptide: binding, signaling and hormone secretion in rodent pituitary cell lines endogenously expressing its receptor - Maixnerová, Jana; Špolcová, Andrea; Pýchová, Miroslava; Blechová, Miroslava; Elbert, Tomáš; Rezáčová, Martina; Zelezná, Blanka; Maletínská, Lenka (Peptides, 2011)
The recently discovered prolactin-releasing peptide (PrRP) binds to the PrRP receptor and is involved in endocrine regulation and energy metabolism. However, its main physiological role is currently unknown. Two biologically active isoforms of PrRP exist: the 31 (PrRP31) and the 20 (PrRP20) amino acid forms, which both contain a C-terminal Phe amide sequence. In the present study, the PrRP receptor was immunodetected in three rodent tumor pituitary cell lines: GH3, AtT20 and RC-4B/C cells. The saturation binding of radioiodinated PrRP31 to intact cells demonstrated a K(d) in the 10(-9)M range and a B(max) in the range of tens of thousands binding sites per cell. For binding to RC-4B/C cells, both PrRP31 and PrRP20 competed with (125)I-PrRP31 with a similar K(i). The C-terminal analog PrRP13 showed lower binding potency compared to PrRP31 and PrRP20. All PrRP analogs increased the phosphorylation of MAPK/ERK1/2 (mitogen-activated phosphorylase/extracellular-regulated kinase) and CREB (cAMP response element-binding protein) in RC-4B/C cells. Additionally, prolactin release was induced by the PrRP analogs in a dose-dependent manner in RC-4B/C cells. Finally, food intake after intracerebroventricular administration of PrRP analogs in fasted mice was followed. Both PrRP31 and PrRP20 decreased food intake, but PrRP13 did not show significant effect. Studies on pituitary cell lines expressing the PrRP receptor are more physiologically relevant than those on cells transfected with the receptor. This cell type can be used as a model system for pharmacological studies searching for PrRP antagonists and stable effective PrRP agonists, as these drugs may have potential as anti-obesity agents.
Keywords: hypofyzární hormony; Male; Cell Line, Tumor; protein vázající cAMP responzivní element; western blotting; fosforylace; signální transdukce; Phosphorylation; molekulární sekvence - údaje; Amino Acid Sequence; Cyclic AMP Response Element-Binding Protein; mužské pohlaví; receptory buněčného povrchu; Signal Transduction; Prolactin-Releasing Hormone; Blotting, Western; Pituitary Hormones; Animals; zvířata; myši inbrední C57BL; Receptors, Cell Surface; sekvence aminokyselin; myši; hormon uvolňující prolaktin; Mice, Inbred C57BL; Molecular Sequence Data; nádorové buněčné linie; Mice